Experimental and in silico evaluation of Carthamus tinctorius L. oil emulgel: a promising treatment for bacterial skin infections - Saeed, Javaria; Hussain Shah, Syed Nisar; Javed, Hina; Aslam, Asma; Ali, Anam; Siddique, Farhan; Zahra, Tahreem; Bin Jardan, Yousef A.; Wondmie, Gezahign Fentahun; Nafidi, Hiba-Allah; Bourhia, Mohammed (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose The current study aimed to develop a topical herbal emulgel containing Carthamus tinctorius L. (CT) oil extract, which has been scientifically proven for its antibacterial and antioxidant activities for the ailment of bacterial skin infections. Method The CT emulgel was formulated by response surface methodology (RSM) and was evaluated by various parameters like extrudability, spreadability, pH, viscosity, and antibacterial and antioxidant activities. Molecular docking was also performed using AutoDock. Results Among all formulated CT emulgels, F9 and F8 were optimized. Optimized formulations had shown good spreadability and extrudability characteristics. Sample F8 had % inhibition of 42.131 ± 0.335, 56.720 ± 0.222, and 72.440 ± 0.335 at different concentrations. Sample F9 had % inhibition of 26.312 ± 0.280, 32.461 ± 0.328, and 42.762 ± 0.398 at concentrations of 250 µg/ml, 500 µg/ml, and 1,000 µg/ml, respectively, which shows that both samples F8 and F9 have significant antioxidant potential. Optimized CT emulgels F8 and F9 had significant antibacterial activity against Staphylococcus aureus and Escherichia coli at p-value = 0.00, the Emulgel-F8 shows zone of inhibition of 24 mm for E-coli and 19 mm for S-aureus. Emulgel-F9 shows zone of inhibition of 22 mm for E-coli and 15 mm for S-aureus while pure CT- Oil extract shows zone of inhibition of 25 mm for E-coli and 20 mm for S-aureus and ciprofloxacin used as standard shows 36mm zone of inhibition against both E-coli and S-aureus. The comparative investigation through molecular docking binding affinities and interactions of ligands with various target proteins provides insights into the molecular processes behind ligand binding and may have significance for drug discovery and design for the current study. Conclusion The current study suggests that C. tinctorius L.-based emulgel has good antioxidant and antibacterial activities against E. coli for the treatment of bacterial skin infections.